Closed Timelike Curves Induced by a Buchdahl-Inspired Vacuum Spacetime in <semantics>R2</semantics> Gravity - Hoang Ky Nguyen; Francisco S. N. Lobo (Universe, 2023)
The recently obtained special Buchdahl-inspired metric Phys. Rev. D 107, 104008 (2023) describes asymptotically flat spacetimes in pure Ricci-squared gravity. The metric depends on a new (Buchdahl) parameter <semantics><mover accent="true">k˜</mover></semantics> of higher-derivative characteristic, and reduces to the Schwarzschild metric, for <semantics><mover accent="true">k˜</mover>=0</semantics>. For the case <semantics><mover accent="true">k˜</mover>∈(−1,0)</semantics>, it was shown that it describes a traversable Morris–Thorne–Buchdahl (MTB) wormhole Eur. Phys. J. C 83, 626 (2023), where the weak energy condition is formally violated. In this paper, we briefly review the special Buchdahl-inspired metric, with focuses on the construction of the Kruskal–Szekeres (KS) diagram and the situation for a wormhole to emerge. Interestingly, the MTB wormhole structure appears to permit the formation of closed timelike curves (CTCs). More specifically, a CTC straddles the throat, comprising of two segments positioned in opposite quadrants of the KS diagram. The closed timelike loop thus passes through the wormhole throat twice, causing two reversals in the time direction experienced by the (timelike) traveller on the CTC. The key to constructing a CTC lies in identifying any given pair of antipodal points <semantics>(T,X)</semantics> and <semantics>(−T,−X)</semantics> on the wormhole throat in the KS diagram as corresponding to the same spacetime event. It is interesting to note that the Campanelli–Lousto metric in Brans–Dicke gravity is known to support two-way traversable wormholes, and the formation of the CTCs presented herein is equally applicable to the Campanelli–Lousto solution.